Dietary Methionine Restriction Reduces Inflammation Independent of FGF21 Action. Issue 8 (17th June 2019) - Sharma, Shaligram; Dixon, Taylor; Jung, Sean; Graff, Emily C.; Forney, Laura A.; Gettys, Thomas W.; Wanders, Desiree
Abstract : Objective: Methionine restriction (MR) decreases inflammation and improves markers of metabolic disease in rodents. MR also increases hepatic and circulating concentrations of fibroblast growth factor 21 (FGF21). Emerging evidence has suggested that FGF21 exerts anti‐inflammatory effects. The purpose of this study was to determine the role of FGF21 in mediating the MR‐induced reduction in inflammation. Methods: Wild‐type and Fgf21 ‐/‐ mice were fed a high‐fat (HF) control or HF‐MR diet for 8 weeks. In a separate experiment, mice were fed a HF diet (HFD) for 10 weeks. Vehicle or recombinant FGF21 (13.6 µg/d) was administered via osmotic minipump for an additional 2 weeks. Inflammation and metabolic parameters were measured. Results: Fgf21 ‐/‐ mice were more susceptible to HFD‐induced inflammation, and MR reduced inflammation in white adipose tissue (WAT) and liver of Fgf21 ‐/‐ mice. MR downregulated activity of signal transducer and activator of transcription 3 in WAT of both genotypes. FGF21 administration reduced hepatic lipids and blood glucose concentrations. However, there was little effect of FGF21 on inflammatory gene expression in liver or adipose tissue or circulating cytokines. Conclusions: MR reduces inflammation independent of FGF21 action. Endogenous FGF21 is important to protect against the development of HFD‐induced inflammation in liver and WAT, yet administration of low‐dose FGF21 has little effect on markers of inflammation.